2008
DOI: 10.1002/pts.841
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of shock and vibration in truck transport in Japan

Abstract: To propose potential lab-simulated vibration tests for developing appropriate cushioning packaging, we recorded vibration acceleration during truck transport, including large sporadic shocks in regular smaller vibration so that acceleration did not cover a normal probability distribution and could not be considered as random vibration. We extracted all shock acceleration from vibration during local road and highway transport and studied the causes. We found that shocks were caused by road roughness, metal join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…Studies have focussed on understanding the characteristics of shocks that occur during road and rail distribution and proposing the development of methods to simulate such characteristics in BRV tests (shock on random testing or real-time high level on time-compressed BRV). [15][16][17][18] These newer developments have demonstrated that conventional BRV tests are not true simulations of the distribution vibration environment and have raised (unanswered) questions over the validity of the single level BRV test. However, the single level test remains the method defi ned by most packaging performance standards.…”
Section: Introductionmentioning
confidence: 97%
“…Studies have focussed on understanding the characteristics of shocks that occur during road and rail distribution and proposing the development of methods to simulate such characteristics in BRV tests (shock on random testing or real-time high level on time-compressed BRV). [15][16][17][18] These newer developments have demonstrated that conventional BRV tests are not true simulations of the distribution vibration environment and have raised (unanswered) questions over the validity of the single level BRV test. However, the single level test remains the method defi ned by most packaging performance standards.…”
Section: Introductionmentioning
confidence: 97%
“…On local roads, the source of the shocks was a result of difference in levels on the asphalt-surfaced road, pedestrian crossings, manholes, road curves, left and right turns, and railroad crossings. This research results suggest that irregularities in road surfaces greatly influence shock levels [4].…”
Section: Shockmentioning
confidence: 67%
“…A safe carriage of goods is often strictly related to safe driving [4]. Highway transportation crashes were the leading cause of fatal injuries in the United States for both workers and the general population from 2003 to 2008, where only truck transportation accounted for 2,320 highway deaths [5].…”
Section: Safety In Transportationmentioning
confidence: 99%
See 1 more Smart Citation
“…The research of Lu et al 7 reports on measurements of truck transport in Japan but concentrates specifi cally on shocks, which are included with the vibration. The paper indicates that the probability distribution function (PDF) of the combined shock and vibration data does not follow a standard normal distribution and, therefore, cannot be considered a truly random vibration.…”
mentioning
confidence: 99%